APLIKASI PENGELOLAAN KAMAR INDEKOS BERBASIS WEB DI KAMAR INDEKOS AL-NAJAH CIPARAY - COMPUTING INFORMATIKA; Rosmalina (Program Studi Teknik Informatika FTI UNIBBA, 2021)
Boarding Room Is a home-based business that provides a place or room for rent to people who need it. Al-Najah Ciparay Boarding Room is one of the boarding houses located in the city of Bandung, to be precise at Kp. Babakan Caringin RT 01 / RW 10 Ciparay Village, Ciparay District. Having been around for more than 20 years, Al-Najah's boarding room still uses manual methods in managing its data.In managing boarding rooms, of course, a good management process is needed to get convenience for both the admin or boarding room manager, as well as service satisfaction for customers or boarding room tenants. With management that is still done manually, of course the boarding house management becomes inefficient and encounters many obstacles, both in terms of promotion, management of admin records, financial management and others.With the discovery of problems and constraints in the boarding room Al-Najah, the author will design a web-based boarding room application using the Waterfall system development method. Broadly speaking, the Waterfall method has steps, namely Requerment Analysis & Specification, Design, Coding and Testing, Integration, Maintenance.The result is a web-based boarding room management application, which can make it easy for prospective tenants to get information about boarding rooms, then the application can also help the admin or boarding room manager in carrying out promotions, data collection, and providing financial reports and others. easily.